Socio-environmental impact of IO and reverse logistics in the textile industry - Méndez Flórez, Manuel
The textile industry is one of the most polluting sectors globally due to its high resource consumption, greenhouse gas emissions, and massive generation of textile waste. With growing concerns about sustainability, reverse logistics emerges as a viable solution to mitigate these environmental impacts. This approach involves the collection, sorting, and recycling of discarded textile products, promoting a circular economy model that minimizes landfill waste, reduces the demand for virgin raw materials, and decreases carbon emissions. However, its implementation faces significant challenges, such as the lack of adequate infrastructure and inconsistencies in the quality of recycled materials. By using advanced multi-criteria decision-making techniques, such as Data Envelopment Analysis (DEA) and fuzzy methods, it is possible to identify and select suitable partners for effectively implementing reverse logistics. This article examines how this strategy can transform the textile industry towards a more sustainable model, highlighting the environmental, economic, and social benefits of integrating it into global supply chains.